ANTIBACTERIAL TEST OF Basil (Ocimum sanctum) LEAF EXTRACT AND FRACTION ON Escherichia coli BACTERIA GROWTH - Sri Ayumi Becerang; Titin Dunggio; Agusrianto Yusuf (Journal of Health, Technology and Science (JHTS), 2022)
The study aims to determine the effect of basil leaf extract and fraction in inhibiting the growth of Escherichia coli bacteria and to determine the best concentration in inhibiting the growth of Escherichia coli bacteria. The methodin this study used a completely randomized design (CRD) with five treatments and five repetitions based on each extract and fraction treatment group, namely: 25% concentration, 50% concentration and 75% concentration. The result shows that from each concentration used from the extract and fraction group, it was found that the largest concentration in inhibiting Eschericia coli bacteria was at a concentration of 75% in the extract group. Statistical analysis of data using Univariate showed no significant difference in values ​​between Fcount and Ftable, therefore it was continued by using the BNT test. Keywords: Basil, Extracts and Fractions, Escherichia coli